National Health Service breast screening programme results for 1991-2. Issue 6900 (7th August 1993) - Chamberlain, J; Moss, S M; Kirkpatrick, A E; Michell, M; Johns, L
Abstract : OBJECTIVES--To report the results of the NHS breast screening programme for the year March 1991 to April 1992. DESIGN--A report of statistics was derived from Körner (K62) returns and from the radiology quality assurance programme. MAIN OUTCOME MEASURES--Detection rates for breast cancer and small (< or = 10 mm diameter) invasive cancer, benign biopsy rates, and recall and acceptance rates. RESULTS--The acceptance rate for screening across the United Kingdom was 71.3%. The referral rate for further investigation was 6.2% (regional 4.3-9.0%). The breast cancer detection rate was 6.2 cancers per 1000 women screened (5.1-9.0) and the detection rate of invasive cancers < or = 10 mm was 1.4/1000 (1.0-2.3). 72% of screening programmes reached the target 70% acceptance rate, and 95% of programmes achieved a recall rate of less than 10%. 75% of programmes had a cancer detection rate of more than 5/1000, but only 32% had a detection rate for invasive cancers < or = 10 mm of more than 1.5/1000. CONCLUSIONS--Overall, the results of the screening programme for the year 1991-2 can be regarded as extremely satisfactory, given the size and complexity of the operation.